Estimation of vessel diameter and blood flow dynamics from laser speckle images - Postnov, Dmitry D. (Biomed Opt Express, 2016)
Laser speckle imaging is a rapidly developing method to study changes of blood velocity in the vascular networks. However, to assess blood flow and vascular responses it is crucial to measure vessel diameter in addition to blood velocity dynamics. We suggest an algorithm that allows for dynamical masking of a vessel position and measurements of it’s diameter from laser speckle images. This approach demonstrates high reliability and stability.